2020
DOI: 10.3390/su12072679
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Improvement Strategy of Competency for Education for Sustainable Development (ESD) of University Teachers Based on Data Mining

Abstract: Competency for ESD (education for sustainable development) of university teachers is the key to the sustainable development of higher education. Developing teachers’ competency for ESD poses a new challenge for Chinese universities. Ideally, a new faculty development system should be established. However, this strategy is not feasible because of cost concerns, and improving competency for ESD by using the existing teacher competency training system is preferred. Therefore, this paper employed a specific data m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
0
19
0
4
Order By: Relevance
“…In the past, research involving the application of data mining techniques has successfully explored sustainability education and development issues [13,14]. This study refers to the data mining techniques developed in the past and uses decision trees to pre-assess the learning effectiveness of the HMEAYC in early childhood education for children with special needs in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, research involving the application of data mining techniques has successfully explored sustainability education and development issues [13,14]. This study refers to the data mining techniques developed in the past and uses decision trees to pre-assess the learning effectiveness of the HMEAYC in early childhood education for children with special needs in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
“…Analysing the objectives of the articles revealed that although most researchers highlighted the importance of integrating ESD competencies into teacher education, 36.4% of articles aimed at presenting or proposing competency frameworks, whereas nearly 24% of articles attempted to introduce an assessment tool along with the competency framework or pedagogical approaches [3,9,30,44,46,[51][52][53], while approximately 12% presented a competency framework only without assessment tools [45,49,54,55].…”
Section: General Overview Of Publications Focused On Esd Competencies In Teacher Educationmentioning
confidence: 99%
“…Moreover, other researchers argued that ESD competencies can serve as standards [54] for curriculum development and could be infused into the programme descriptors [19] whether as educational goals [9] or learning outcomes [48,63,64]. In addition, ESD competency can be addressed as a new indicator within the existing teacher competency model [52].…”
Section: Approaches To Integrate Esd Key Competencies Into Teacher Education Programmesmentioning
confidence: 99%
“…Kompetensi profesional keguruan ESD yang dikenal pasti daripada SLR yang dilakukan adalah melibatkan pengetahuan profesional ESD guru iaitu pengetahuan isi kandungan ESD guru (PIK-ESD) (Anđić, 2020;Bagoly-Simó et al, 2017;Bertschy et al, 2013;Brandt et al, 2019;Bürgener & Barth, 2017;Dumitrescu et al, 2014;Lambrechts et al, 2013;Liu & Qi, 2021;Malandrakis et al, 2018;Mróz et al, 2018;Ofei-Manu & Didham, 2018;Rauch & Steiner, 2013;Rosenkränzer et al, 2017;Timm & Barth, 2020;Weng et al, 2020) dan juga pengetahuan pedagogi-isi kandungan ESD guru (PPIK-ESD) (Bagoly-Simó et al, 2017;Bertschy et al, 2013;Brandt et al, 2019;Bürgener & Barth, 2017;Dumitrescu et al, 2014;Fedosejeva et al, 2018;Garrido et al, 2020;Kaya et al, 2021;Liu & Qi, 2021;Malandrakis et al, 2018;Mogensen & Schnack, 2010;Naji, 2015;Ofei-Manu & Didham, 2018;Ou et al, 2021;Rauch & Steiner, 2013;Rosenkränzer et al, 2017;Sund, 2015;Timm & Barth, 2020;Weng et al, 2020). PIK-ESD guru adalah berbeza dengan PPIK-ESD guru tetapi PIK-ESD diperlukan guru untuk membentuk PPIK-ESD mereka (Rosenkränzer et al, 2017).…”
Section: Kompetensi Profesional Keguruan Esdunclassified